International entrepreneurial behavior of internationalizing African SMEs – Towards a new research agenda - Zahoor, Nadia; Khan, Zaheer; Meyer, Martin; Laker, Benjamin (Elsevier, 2022)
Research on the international entrepreneurial behavior of small and medium-sized enterprises (SMEs) originating from Africa has been receiving growing scholarly attention. Despite a proliferation of studies on the subject, the literature has hitherto remained fragmented, theoretically limited, and empirically inconclusive, thereby leaving important topics underexplored. This paper seeks to address this shortcoming through a systematic literature review aimed at critically analyzing and synthesizing 66 articles published in leading journals from 1995 to 2021. Our paper describes how research on the international entrepreneurial behavior of African SMEs has evolved over time, and identifies key gaps in the existing literature, thereby pointing at future avenues for research. By mapping descriptive findings in terms of methods, geography, and theoretical perspectives, we further develop an integrative framework suited to frame insights drawn from the current literature and offer important opportunities for future research on internationalizing SMEs originating from Africa.
Keywords: International entrepreneurial behavior; Internationalization; SMEs; International new ventures; Systematic review; Africa